Retraction notice to "Si RNA inhibition of GRP58 associated with decrease in mitomycin C-induced DNA cross-linking and cytotoxicity": [Chem. Biol. Interact. 162/1 (2006) 81–87]. (1st October 2018) - Su, Shibing; Adikesavan, Anbu Karani; Jaiswal, Anil K.
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of the Office of Integrity of the University of Maryland due to data entered in Fig 3 of the publication that were not supported by raw data, in addition to the fact that the statistical evaluations were adultered.